Tannin-based wood panel adhesives - Oktay, Salise; Pizzi, Antonio; Köken, Nesrin; Bengü, Başak (Elsevier BV, 2024)
The wood-based panel industry provides industrial-scale production of engineered wood products for our daily life. In the production of wood-based panels, the most important input other than wood raw material is the adhesive. Formaldehyde-based resins are used as binders in the production of wood-based panels thanks to their cost and reactivity advantages. However, their fossil origin and formaldehyde content have increased the interest in resin synthesis studies with the use of biobased materials. Tannin is one of the most studied raw materials both in academia and industry to synthesize bio-based wood adhesives due to the suitability of its chemical structure and availability. In this review, the developed tannin-based wood resin formulations that have been developed were examined in two main sections. These are crosslinked tannin-based resins developed using crosslinkers such as hexamine, furfural, etc. And hybrid tannin-based resins prepared using other biobased resources such as starch, lignin, etc. The performance of the developed resin formulations was evaluated on the mechanical and physical properties of the final product such as particleboard and plywood. The pros and cons of each resin formulation were examined in detail regarding the final product performances. All of the obtained results showed that bio-based resin formulations synthesized with tannin and without formaldehyde have the potential to compete with formaldehyde-based resins.